The recomposition of post-pandemic learning through a mathematical modeling activity: System of equations of the first degree - Baumgarten, Elisandro Rafael (Seven Editora, 2023)
This article reports an activity of recomposition of learning carried out in the ninth years of the State High School Castelo Branco, in the Municipality of Três de Maio-RS. The need for the activity was due to not having been worked in the previous school year the content of linear system of two equations of the first degree, so it was developed an activity of recovery of the contents of Cartesian plan and equation of the first degree that had their results compromised due to the COVID-19 pandemic, together with the activity of recomposition of learning for the subsequent continuation of the contents of the matrix of the current school year. The activity also had the assumptions of Mathematical Modeling in education, in which students were introduced to this practice, comprising its three main stages: perception and apprehension, understanding and explicitness and signification and expression (BIEMBENGUT, 2016). The Activity also remains supported by the theory of dialogicity (FREIRE, 2019), through which it is understood that the student, as an individual in development, becomes (co)author of knowledge through dialogue with the teacher and with other students in the classroom. It was verified the importance of performing this type of activity through the difficulty that the student, especially from elementary school, has in externalizing his thinking and his conclusions about any activity, concluding that the textual production and presentation by the student reporting what was developed in the activity helps the process of exteriorization. The realization of the activity in the classroom counted on expository activities and mathematical modeling through problem-situations proposed for group work and subsequent preparation of report and presentation to the class. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-019